ANALYSIS OF CONTROL FOR PRIMARY RAW MATERIAL INVENTORY USING EOQ, POQ, & LFL METHODS - Iskandar Iskandar; Octaria Marsha Ananda (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2024)
Inventory is the goods that a company plans to own, acquired through purchase or production, with the aim of being marketed to consumers. Companies must be able to overcome challenges in controlling goods to achieve the desired target by minimizing the costs incurred and maximizing the profits obtained by the company. There are three methods that can be used to manage raw material inventory, namely EOQ, POQ, and LFL. This research aims to analyze, using the EOQ, POQ, and Lot For Lot methods, the possibility of supply chain resilience for a company operating in the short-lived perishable food industry. The results show that inventory cost savings for raw materials using the POQ method can achieve the largest savings of up to 6.78% compared to the company's current method. Savings in ordering costs with the EOQ method result in the highest savings, namely 88.68% compared to the company's current method. As for savings in storage costs, the method that was applied showed that the Lot For Lot (LFL) method is 0.6% more cost-effective compared to the company's current method, as well as the POQ and EOQ methods. The POQ method is identified as the one that minimizes raw material inventory costs, amounting to Rp 375,005,043.